Beyond the wall : chapters on urban Jerusalem - Zaun-Goshen, Heike (Ibidem-Verlag, 2019)
Beyond the Wall sheds light on some of the enigmas of Jerusalem's more recent past, telling the tale of its growth from a provincial town somewhere in the Turkish Empire into a modern city. The book also includes two chapters on Arab Jerusalem and a preface by Teddy Kollek, who served as the city's mayor for almost thirty years.